Назустріч іншій міфології. Витвір темряви: доньки та внуки йокасти - Лозиця І. (Народна творчість та етнологія, 2011)
The aim of the articleis write an essay about the personal vision of the state and tendencies of the mythological researches in Croatian science, using a wide theoretical base, without any claims to complete it or to give the universal confession. The article highlights author’s personal opinions and comments on the mentiones subject. Namjera mi je iz šireg teorijskog rakursa skicirati vlastito viđenje stanja i tendencija mitoloških istraživanja u hrvatskoj znanosti, dakako bez pretenzija na potpunost ili univerzalno prihvaćanje. Riječ je o osobnoj prosudbi, o radnome komentaru.